ASME 2018 12th International Conference on Energy Sustainability 2018
DOI: 10.1115/es2018-7197
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Emissions of a CRDI Passenger Van Using CME-Diesel Blends

Abstract: In a move to reduce dependence on imported fossil fuels, develop and utilize indigenous renewable and sustainably-sourced clean energy sources, the Philippines enacted the Biofuels Act of 2006 (or Republic Act 9367) that mandated blending of biodiesel with commercially sold diesel fuels which presently is at 2% coconut methyl ester (CME) by volume. Deliberations are underway to shift to 5% by volume so that data on the effects on performance and emissions of percentage blends are necessary. This study presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Carbon monoxide and total hydrocarbon emissions also reduced with increasing blend rates. Study results also showed that 5% CME is the optimum blend rate in terms of fuel economy and emissions improvement (Quiros, et al, 2018).However, more studies will be needed using different vehicle types to strengthen the claim that CME is a viable fuel enhancer and/ or substitute. Meanwhile, Alonzo (2016), in his economic and environmental analysis of the impact of higher-blended biodiesel on the Philippine economy, determined the environmental and health benefits of increasing the blend rate from 2% to 5% CME, which amounted to PhP 7 -26 million and PhP 472 million, respectively.…”
Section: Viability Of Cme As Biodiesel Feedstockmentioning
confidence: 89%
“…Carbon monoxide and total hydrocarbon emissions also reduced with increasing blend rates. Study results also showed that 5% CME is the optimum blend rate in terms of fuel economy and emissions improvement (Quiros, et al, 2018).However, more studies will be needed using different vehicle types to strengthen the claim that CME is a viable fuel enhancer and/ or substitute. Meanwhile, Alonzo (2016), in his economic and environmental analysis of the impact of higher-blended biodiesel on the Philippine economy, determined the environmental and health benefits of increasing the blend rate from 2% to 5% CME, which amounted to PhP 7 -26 million and PhP 472 million, respectively.…”
Section: Viability Of Cme As Biodiesel Feedstockmentioning
confidence: 89%